2021
DOI: 10.3233/wor-208022
|View full text |Cite
|
Sign up to set email alerts
|

Comfort and discomfort during smartphone use on a bed

Abstract: BACKGROUND: The number of smartphone users is immense. People can do ever more with a smartphone. Smartphones are used everywhere, including in bed and on the sofa. The awkward postures taken in these situations affect comfort and discomfort. In designing a bed, it might be useful to know which position is comfortable for smartphone use on a bed. OBJECTIVE: The objective was to define the most comfortable trunk angle for smartphone use on a bed. METHODS: To study comfort and discomfort, 52 participants were as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…37,38 Also, higher flexion angles cause NMSD with postural stress and muscular imbalances, resulting in anatomical structure deformation and nerve compression. 39,40 The limitations of the study are the FEA model, generated through CT images, pertains to one patient. Thus, the analysis is patient-specific.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…37,38 Also, higher flexion angles cause NMSD with postural stress and muscular imbalances, resulting in anatomical structure deformation and nerve compression. 39,40 The limitations of the study are the FEA model, generated through CT images, pertains to one patient. Thus, the analysis is patient-specific.…”
Section: Discussionmentioning
confidence: 99%
“…37,38 Also, higher flexion angles cause NMSD with postural stress and muscular imbalances, resulting in anatomical structure deformation and nerve compression. 39,40…”
Section: Discussionmentioning
confidence: 99%
“…There are many possible postures for people holding smartphones, such as double-hand and single-hand holding. The smart phones are used for many activities such as texting, playing games or listening to music [1]. Udomboonyanupap, et al [1] also showed that the right hand and double hand (texting with thumbs) are used mostly for texting.…”
Section: Methodsmentioning
confidence: 99%
“…The smart phones are used for many activities such as texting, playing games or listening to music [1]. Udomboonyanupap, et al [1] also showed that the right hand and double hand (texting with thumbs) are used mostly for texting. That is why these positions were selected.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation